Two chemosensory operons of Rhodobacter sphaeroides are regulated independently by sigma 28 and sigma 54. - Martin, A; Gould, M; Byles, E; Roberts, M; Armitage, J (2006)
Rhodobacter sphaeroides has a complex chemosensory system, with several loci encoding multiple homologues of the components required for chemosensing in Escherichia coli. The operons cheOp2 and cheOp3 each encode complete pathways, and both are essential for chemosensing. The components of cheOp2 are predominantly localized to the cell pole, whereas those encoded by cheOp3 are predominantly targeted to a discrete cluster in the cytoplasm. Here we show that the expression of the two pathways is regulated independently. Overlapping promoters recognized by sigma(28) and sigma(70) RNAP holoenzyme transcribe cheOp2, whereas cheOp3 is regulated by one of the four sigma(54) homologues, RpoN3. The different regulation of these operons may reflect the need for balancing responses to extra- and intracellular signals under different growth conditions.